EFFECT OF LOW-, MODERATE-, AND HIGH-INTENSITY EXERCISE ON ATRIAL NATRIURETIC PEPTIDE (ANP) AND SARCOPLASMIC/ENDOPLASMIC RETICULUM CALCIUM-ATPase 2a (SERCA2a) GENE EXPRESSION IN WISTAR RAT CARDIAC MUSCLE - Averina Octaxena Aslani; Hanna Goenawan; Nova Sylviana (PAIFORI, 2019)
Exercise is one of the factors that affect cardiovascular health. Exercise has been proven to reduce the number of cardiovascular diseases. However, it is also known that doing intense exercise has an adverse effect on heart health which can increase the risk of cardiovascular disease. While doing exercise, there is compensation from the heart itself by producing substances to maintain the heart to remain functional, known as cardiac biomarkers, including ANP and SERCA2a. Thus far, the recommended intensity is moderate-intensity exercise, which is optimal for heart health, but this recommendation has not been supported by biomolecular study. Therefore, this research was conducted. This study was done using semi-quantitative analytic method and experimental study design. Total of 24 male wistar rats were divided randomly into 4 groups: 1 control group (0m/min) and 3 exercise groups (low-: 10m/min, moderate-: 20m/min, high- intensity exercise: 30m/min). All groups received 30 min/day running, 5x/week for 12 weeks. The rats were terminated under anaesthesia, cardiac muscle extraction was done from left ventricle, and gene expression of ANP and SERCA2a is studied. Statistical analysis was done using SPSS software with one-way ANOVA followed by post hoc comparisons if the p-values < 0.05. The expression of ANP increased but insignificant in low-, moderate-, and high-intensity exercise group of rat (0.872±0.034 vs 0.901±0.018 vs 0.916±0.015 vs 0.938±0.025; p=0.304). The expression of SERCA2a also increased insignificantly in low-, moderate-, and high-intensity exercise group of rat (1.044±0.019 vs 1.051±0.015 vs 1.063±0.011 vs 1.082±0.027; p=0.493). Different exercise intensity didn’t have significant effect on ANP and SERCA2a expression in rat cardiac muscle.